2021
DOI: 10.1186/s12876-021-01883-6
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: real-world data rates of deep remission with anti-TNFα in inflammatory bowel disease

Abstract: Background Deep remission (DR) is a treatment target in IBD associated with reduced hospitalization and improved outcome. Randomized control trial (RCT) data demonstrates efficacy of anti-TNFα agents in achieving DR; however, real-world data (RWD) can provide information complementary to RCTs, specifically regarding treatment duration. In this systematic review with meta-analysis, we use real-world data (RWD) to determine rates of DR in IBD treated with anti-TNFα. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…This study's findings agree with the previous indirect meta-analyses that reported the superiority of IFX in the induction phase in terms of significantly better clinical response [ 4 - 11 ]. This superiority was particularly evident given that out of the three studies that assessed induction phase clinical response [ 15 , 23 , 25 ], two studies reported significantly higher baseline disease severity in the IFX group [ 23 , 25 ].…”
Section: Reviewsupporting
confidence: 92%
See 1 more Smart Citation
“…This study's findings agree with the previous indirect meta-analyses that reported the superiority of IFX in the induction phase in terms of significantly better clinical response [ 4 - 11 ]. This superiority was particularly evident given that out of the three studies that assessed induction phase clinical response [ 15 , 23 , 25 ], two studies reported significantly higher baseline disease severity in the IFX group [ 23 , 25 ].…”
Section: Reviewsupporting
confidence: 92%
“…Notably, there was an equal clinical response (OR = 1) and quite equal mucosal healing in the two groups (OR = 0.99). These findings are supported by previously reported comparable efficacy of both drugs at the maintenance phase [ 4 - 11 ].…”
Section: Reviewsupporting
confidence: 91%
“…Whilst the field of IBD has stepped away from symptom control as the only treatment target to a more stringent target of tissue healing on the level of endoscopy, histology, and barrier function, deep mucosal healing remains an elusive target in many UC patients. 57 For example, there is an increasing body of evidence that suggests that achieving histological remission [traditionally defined by resolution of neutrophilic inflammation] in UC patients is associated with a reduced risk of clinical relapse, corticosteroid use, hospitalization, and colectomy compared with achieving clinical remission or even endoscopic remission alone. 58–60 In systematic reviews of pharmacological therapies in RCTs for UC, histological remission is achieved in ~60% of patients treated with 5-ASA.…”
Section: Identifying Appropriate Uc Patients For Early Escalationmentioning
confidence: 99%
“…Only one [23] of the included studies utilised very specific tools for methodological quality assessment. Three [24][25][26] of the included studies employed validated QA tools. In order to validate the tools used in the included studies, they employed 39 non-randomised studies [24], 131 cohort studies [25] and 30 cost-effectiveness studies [26].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Three [24][25][26] of the included studies employed validated QA tools. In order to validate the tools used in the included studies, they employed 39 non-randomised studies [24], 131 cohort studies [25] and 30 cost-effectiveness studies [26]. On the other hand, the QA tools utilised to the remaining thirteen of the included studies were not validated.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%